2017
DOI: 10.1002/cam4.1037
|View full text |Cite
|
Sign up to set email alerts
|

StrandAdvantage test for early‐line and advanced‐stage treatment decisions in solid tumors

Abstract: Comprehensive genetic profiling of tumors using next‐generation sequencing (NGS) is gaining acceptance for guiding treatment decisions in cancer care. We designed a cancer profiling test combining both deep sequencing and immunohistochemistry (IHC) of relevant cancer targets to aid therapy choices in both standard‐of‐care (SOC) and advanced‐stage treatments for solid tumors. The SOC report is provided in a short turnaround time for four tumors, namely lung, breast, colon, and melanoma, followed by an investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…To test whether assays that interrogate a fraction of the exome can identify iCAM+ tumors, the mutational burden of TCGA tumors was recomputed by restricting the data to genomic regions assayed by two commercial assays: FoundationOne 6 (315/236 genes, http://foundationone.com) and StrandAdvantage 15 (selected regions of 152 genes, https://www.strandcenters.com/strand-advantage/). ROC curves (Figure 3) for iCAM+ versus iCAM− class prediction of tumors from TCGA using mutations sequenced by these assays (Data Supplement) showed that FoundationOne 6 (AUC: 0.85-0.99) and StrandAdvantage 15 (AUC: 0.78-0.98) can identify iCAM+ tumors accurately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To test whether assays that interrogate a fraction of the exome can identify iCAM+ tumors, the mutational burden of TCGA tumors was recomputed by restricting the data to genomic regions assayed by two commercial assays: FoundationOne 6 (315/236 genes, http://foundationone.com) and StrandAdvantage 15 (selected regions of 152 genes, https://www.strandcenters.com/strand-advantage/). ROC curves (Figure 3) for iCAM+ versus iCAM− class prediction of tumors from TCGA using mutations sequenced by these assays (Data Supplement) showed that FoundationOne 6 (AUC: 0.85-0.99) and StrandAdvantage 15 (AUC: 0.78-0.98) can identify iCAM+ tumors accurately.…”
Section: Resultsmentioning
confidence: 99%
“…ROC curves (Figure 3) for iCAM+ versus iCAM− class prediction of tumors from TCGA using mutations sequenced by these assays (Data Supplement) showed that FoundationOne 6 (AUC: 0.85-0.99) and StrandAdvantage 15 (AUC: 0.78-0.98) can identify iCAM+ tumors accurately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two hundred nanograms was used as input for the SA152 panel while 20‐40 ng was used for the Swift panel. Somatic variants were identified and prioritized using Strand's proprietary tools, Strand NGS (http://www.strand-ngs.com), and StrandOMS (previously StrandOmics), respectively . Sixty‐four lung cancer samples were tested for EGFR mutations on cobas EGFR Mutation Test v2 (Roche Molecular Systems, Inc, CA, USA) at source.…”
Section: Methodsmentioning
confidence: 99%